VARROOSIS DISTRIBUTION OF HONEYBEES IN THE POLTAVA REGION - Nazarenko, O. S.; Yevstafieva, V. О. (Scientific Progress & Innovations, 2019)
Modern beekeeping is an important branch of agriculture in different countries of the world, in particular in Ukraine, which provides pollination of entomophilous crops, production of honey, wax and other beekeeping products for the needs of the population, food, medical, chemical and other industries. Infectious and non-contagious illnesses of bees and their breeding grounds, which cause significant losses to beekeeping, are the main obstacle to the development of the industry. Such illnesses also include varroosis, which is a global problem for beekeeping, as the invasion leads to a weakening and diminishing in the number of bee colonies, negative impact on the environment, lower yields of entomophilic crops and overall productivity of the industry as a whole. Scientists note that in recent years, the Varroa destructor parasite is one of the most dangerous pests of honeybees (Apis mellifera). The research was carried out on the basis of the Laboratory of Parasitology and Veterinary-Sanitary Expertise at the Poltava State Agrarian Academy and in the conditions of 424 individual peasant and farm farms of the Poltava region (Hrebinka, Lubny, Zinkiv, Kotelva, Novi Sanzhary, Orzhytsia, Pyriatyn, Poltava, Reshetylivka districts). According to the results of parasitological studies, it has been established that varroosis of honeybees are a common invasion in the territory of the studied region, the the average infection of bee colony is 48.71 % at fluctuations of indicators from 16.66 to 100.00 %. Moreover, 83.25 % of investigated farms were not well-versed with varroosis. It has been determined that varroosic invasion in honeybees in 61.34 % of cases occurs in association with other invasive diseases such as nosemosis, acaraposis and amebiasis. Varroosic monoinvasion is detected in 38.66 % of cases. Mixinvasions consisted of two- (51.88 %) and threecomponent (9.46 %) associations of pathogens of invasion. Frequently diagnosed with varroosic-nosemosic invasion (78.46 %). Less commonly, there were varroosic-nosemosic-acaraposic (8.39 %), varroosicnosemosic- amebiasic (7.03 %), varroosic-acaraposic (5.21 %) and varroosic-amebiasic (0.91 %) invasions. The obtained results of research will increase the effectiveness of planning of medical and preventive measures in beekeeping.